Pemberdayaan Masyarakat Berbasis Masjid dalam Perspektif Dakwah Nabi saw. - Cucu Nurjamilah (Journal of Islamic Studies and Humanities, 2016)
Da’wah of social empowerment is the real action in order to make the improvements. Historically, da’wah in the form of social empowerment based on mosque has been portrayed by the Prophet in the Nabawi Mosque Madinah. Muhammad saw. has successfully repaired and changed the conditions of the Medina people into a new powerfull society. Forms of empowerment included empowering spiritual aspect, social (of unity and equality), education, economics, politics and defense. The steps in empowerment, was to grow and to build the spiritual potential of Tawheed communities, providing access to (social institutions) building a mosque, made peace agreement with the various parties, established markets around the mosque, formed and trained defense forces, and togetherness.Dakwah pemberdayaan masyarakar merupakan gerakan dakwah yang bersifat tindakan nyata, guna mewujudkan perubahan. Secara historis, dakwah dalam bentuk pemberdayaan masyarakat berbasis masjid telah diperankan oleh Rasulullah saw. di Masjid Nabawi Madinah. Nabi telah mampu memperbaiki dan mengubah kondisi masyarakat Madinah dan sekitarnya menjadi sebuah masyarakat baru yang maju dari semua sisi. Bentuk pemberdayaan yang dilakukan meliputi pemberdayaan dalam aspek spiritual, aspek sosial (persatuan dan kesetaraan), pendidikan, ekonomi, politik dan pertahanan. Adapun langkah yang ditempuh dalam melakukan pemberdayaan, adalah menumbuhkan dan membangun potensi spiritual Tauhid masyarakat, menyediakan akses (pranata sosial) dengan: membangun masjid, membuat perjanjian damai dengan berbagai pihak, mendirikan pasar di sekitar masjid, membentuk dan melatih pasukan pertahanan, dan kebersamaan.